Event rewind: Learning support for a multi-country climate resilience programme for food security - Hassain, Arif; van Gilst, Daniel; Leight, Jessica; de Brauw, Alan; Laderach, Peter; Mekuria, Wolde; Kamau, David; Grassini, Christian; Philip, Serene; Timothy, Adeyinka Jacob; Ochuma, Lynett; Kosec, Katrina; et al. (International Food Policy Research Institute, 2024)
Organized by CGIAR with support from World Food Programme (WFP) and The Norwegian Agency for Development Cooperation (Norad)